Is There Any Association between Helicobacter pylori CagA Status and Patient’s Habits with Gastric Carcinoma - Hassan, Md Ali; Ahad, Md Abdul; Rahman, Md Habibur; Bhuiyan, Md Sohrab Hossain; Khan, Md Amzad Hossain (Faridpur Medical College Journal, 2016)
Enormous studies have been conducted worldwide regarding CagA+ status of H. pylori and patients habits in gastric carcinoma. But no study has been carried out in our country yet. Thus, this study has been designed to see the association between CagA+ H. pylori strain and patients habits with gastric carcinoma. For this purpose, a total number of 80 (eighty) patients were selected. Of the 80 (eighty) patients 40 (forty) were selected as cases (malignant) and the remainder 40 (forty) were selected as controls (non-malignant). H. pylori was detected by applying noninvasive (H. pylori IgG serology and CagA IgG serology) and invasive (Histology and rapid urease test) technique. Of them Histology was done by Modified Giemsa stain, CagA IgG was detected by ELISA method. In this study, we see that among the 40 cases, 35 (thirty five) possess the CagA+ H. pylori strain. And among the 40 controls, 33 (thirty three) bear the CagA+ H. pylori strain. This study also discloses that among cases, who were habituated with betel leaf and betel-nut ranking the highest number of gastric carcinoma. There are sufficient papers in favor of it which argues that CagA positivity as well as H. pylori positivity is not the sole causative agent of gastric carcinoma. If so, it merely acts as an initiator. Faridpur Med. Coll. J. Jan 2015;10(1): 9-13